Use of GC Clamps in DHPLC Mutation Scanning - Wurzburger, Robert J. (Marshfield Clinic Research Foundation, 2003)
OBJECTIVE: Development of a systematic mutation detection assay strategy for denaturing high performance liquid chromatography (DHPLC). DESIGN: Adaptation of Guanine and Cytosine (GC)-clamping from denaturing gradient gel electrophoresis (DGGE) to DHPLC. METHODS: Three target sequences harboring known allelic variants were studied to develop a general DHPLC assay design strategy. These were exon 10 of the human RET (REarranged during Transfection) gene, exon 52 of the mouse Col1a2 gene, and exon 9 of the human FAS (APO-1, CD-95) gene. Available software was used to analyze melting curves and determine assay conditions. GC clamps of 20 bp or 36 bp were added to polymerase chain reaction (PCR) primers to introduce a high melting temperature (T(m)) domain to each of the target molecules. DHPLC was performed under partially denaturing conditions. RESULTS: DHPLC assays of PCR-amplified sequences can be developed using a personal computer. The following three steps allowed for mutation detection in all three targets. 1. The target sequence should have a uniform T(m.) 2. GC clamps of length sufficient to introduce a second melting domain with a T(m) ≥ 8° above that of the target sequence should be appended to one of the primers. 3. The DHPLC assay should be performed at the highest temperature at which the target sequence is predicted to be ≥ 90% double stranded. CONCLUSION: Addition of GC-clamps to primers facilitates mutation detection by DHPLC. The theoretical basis for this observation is identical to that underlying the utility of GC-clamps in DGGE.